MyPlate Nutrition Education Series: Men’s Health: Get the Facts to Feel and Look Better - Linda B. Bobrof (EDIS)
After introducing MyPlate in June 2011, USDA provided a series of one-page fact sheets to help consumers use the dietary advice of the Dietary Guidelines 2010. The USDA added new fact sheets in December 2011 and continued adding fact sheets in 2012, 2013, and 2014. These fact sheets are distributed by UF/IFAS Extension for Extension faculty, health professionals, and consumers. They are also called the “Ten Tips Nutrition Education Series” and “DG TipSheets." This 2-page fact sheet was written by the USDA Center for Nutrition Policy and Promotion, with an Introduction by Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, May 2014.